2007
DOI: 10.1038/sj.bjc.6603796
|View full text |Cite
|
Sign up to set email alerts
|

High-grade clear cell renal cell carcinoma has a higher angiogenic activity than low-grade renal cell carcinoma based on histomorphological quantification and qRT–PCR mRNA expression profile

Abstract: Clear cell renal cell carcinoma (CC-RCC) is a highly vascularised tumour and is therefore an attractive disease to study angiogenesis and to test novel angiogenesis inhibitors in early clinical development. Endothelial cell proliferation plays a pivotal role in the process of angiogenesis. The aim of this study was to compare angiogenesis parameters in low nuclear grade (n ¼ 87) vs high nuclear grade CC-RCC (n ¼ 63). A panel of antibodies was used for immunohistochemistry: CD34/Ki-67, carbonic anhydrase IX, hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
43
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 33 publications
6
43
0
1
Order By: Relevance
“…As summarized in Table 1, higher MVD has been reported in many studies to be a favorable prognostic factor (eg, a higher blood vessel density in CCRCC is correlated with a better prognosis or longer patient survival). 4,[14][15][16][17][18][19][20][21][22] However, other studies have reported opposite results correlating higher MVD with poorer prognosis, [23][24][25][26][27][28] whereas others have been unable to find a significant prognostic role for MVD. [29][30][31][32][33] The controversy could result from many nonmechanistic factors, including sample size, sampling bias, the different blood vessel markers chosen for immunohistochemical (IHC) characterization, the quality of IHC staining, the methods of vasculature quantification, and the methods of interpretation.…”
Section: Differential Analysis Of Tumor Vasculaturementioning
confidence: 56%
“…As summarized in Table 1, higher MVD has been reported in many studies to be a favorable prognostic factor (eg, a higher blood vessel density in CCRCC is correlated with a better prognosis or longer patient survival). 4,[14][15][16][17][18][19][20][21][22] However, other studies have reported opposite results correlating higher MVD with poorer prognosis, [23][24][25][26][27][28] whereas others have been unable to find a significant prognostic role for MVD. [29][30][31][32][33] The controversy could result from many nonmechanistic factors, including sample size, sampling bias, the different blood vessel markers chosen for immunohistochemical (IHC) characterization, the quality of IHC staining, the methods of vasculature quantification, and the methods of interpretation.…”
Section: Differential Analysis Of Tumor Vasculaturementioning
confidence: 56%
“…Although Ang-1 mRNA levels in the tumor were approximately 25% less compared with their levels in normal kidney tissue, Ang-2 mRNA was increased over 30-fold in the tumor. A similar shift in angiopoietin balance was recently reported in RCC by Baldewijns et al 16 Although mRNA levels of different genes cannot be directly compared, the change in Ang-1/-2 mRNA ratio implies a shift toward a vessel destabilization phenotype. The increased mRNA levels of Ang-2 in RCC were corroborated by western blot analysis, showing significant amounts of Ang-2 protein in this tumor type.…”
Section: Resultsmentioning
confidence: 73%
“…JMJD1A is especially located around vessel of cancer tissue, which suggest that JMJD1A may be involved in VEGFA expression. The overexpression of VEGFA is beneficial for tumor angiogenesis and RCC is a highly vascularized cancer [19], so regulation of JMJD1A on VEGFA may be important for RCC development. …”
Section: +mentioning
confidence: 99%